Does visual appeal moderates the impact of attitude towards advertising on brand attitude, attachment and loyalty? - Sufyan Ramish, Muhammad (2023)
Purpose – The aim of this study is to investigate the influence of consumers’ attitude towards advertising on brand attitude, brand loyalty and brand attachment. The study delineates two pathways; the first is an indirect link of attitude towards advertising on brand attachment and brand loyalty through brand attitude, while the second pathway focuses on the moderating role of visual appeal of stock photography on the relationship between attitude towards advertising, brand attitude, brand loyalty and brand attachment. Design/methodology/approach – The data of study were gathered in two-time lags from 431 customers of Islamic banks in Pakistan. The proposed hypotheses were examined using structural equation modeling. Findings – The finding of the study revealed that attitude towards is indirectly related to brand loyalty and brand attachment through brand attitude. The study also found that attitude towards advertising is positively related to brand attitude, brand loyalty and brand attachment and these paths also moderated by visual appeal of stock photography. Practical implications- The paper provides guidelines to the advertiser and management of Islamic banks to decide to attract more customers with low cost by focusing on visual appeal of stock photography.  Originality/value – Previous studies have overlooked the potential influence of attitude towards advertising on brand loyalty and brand attachment through brand attitude. The current study addresses this gap by examining brand attitude as a mediator between these relationships. The study also explored the moderating role of visual appeal in explaining the consumers’ attitude towards advertising and brand.